Subtle Alterations in Spatial Memory Induced by Amyloid Peptides Infusion in Rats - Macêdo, Priscila Tavares; Aquino, Antônio C. Q.; Meurer, Ywlliane S. R.; Brandão, Luiz E. M.; Campêlo, Clarissa L. C.; Lima, Ramon H.; Costa, Marcos R.; Ribeiro, Alessandra M.; Silva, Regina H. (Frontiers in Aging Neuroscience, 2018)
The cause of Alzheimer’s disease (AD) remains uncertain. The accumulation of amyloid peptides (A) is the main pathophysiological hallmark of the disease. Spatial deficit is an important initial sign of AD, while other types of memory impairments that appear in later stages. The Barnes maze allows the detection of subtle alterations in spatial search by the analysis of use of different strategies. Previous findings showed a general performance deficit in this task following long-term (35 days) infusion of A, which corresponds to the moderate or severe impairments of the disease. In the present study, we evaluated the effects of a low-dose 15-day long treatment with A peptides on spatial and non-spatial strategies of rats tested in the Barnes maze. A peptides (0.5L/site/day; 30pmoL solution of A1-40:A1-42 10:1) or saline were bilaterally infused into the CA1 (on the first treatment day) and intraventricularly (on the following 15 days) in six-month-old Wistar male rats. A infusion induced a deficit in the performance (increased latency and distance traveled to reach the target compared to saline group). In addition, a significant association between treatment and search strategy in the retrieval trial was found: A group preferred the non-spatial search strategy, while saline group preferred the spatial search. In conclusion, the protocol of A infusion used here induced a subtle cognitive deficit that was specific to spatial aspects. Indeed, animals under A treatment still showed retrieval, but using non-spatial strategies. We suggest that this approach is potentially useful to the study of the initial memory deficits in early AD.